The development of a primary core French program for the province of Newfoundland and Labrador - Templeman, Karen L., 1969- (2000)
Thesis (M.Ed.)--Memorial University of Newfoundland, 2000. Education Bibliography: leaves 46-48 The purpose of this project was to develop a primary Core French program to meet the needs of students and teachers in the primary grades (English stream) in the schools of Newfoundland and Labrador. The project report contains a development plan that describes the rationale for the proposed program in terms of background information, needs, and problem analysis. The procedure and methodology for conducting a needs assessment is discussed, followed by a description and analysis of the results of the survey/questionnaire distributed to 390 primary teachers within the Avalon East School Board. The results of the survey/questionnaire combined with information gleaned from the literature review form the basis for development of the primary Core French program. The components of the program are discussed, specifically the curriculum guide that is the final and major component of the project The report concludes with a summary of points that describe the purpose and potential value of the proposed program, followed by recommendations for its implementation and evaluation.